Observational study of pimecrolimus 1% cream for prevention of transcutaneous sensitization in children with atopic dermatitis during their first year of life - Murashkin, Nikolay N.; Namazova-Baranova, Leyla S.; Makarova, Svetlana G.; Ivanov, Roman A.; Grigorev, Stepan G.; Fedorov, Dmitri V.; Ambarchian, Eduard T.; Epishev, Roman V.; Materikin, Alexander I.; Opryatin, Leonid A.; Savelova, Alena A. (Frontiers in Pediatrics, 2023)
Epidermal barrier dysfunction in children with atopic dermatitis can cause transcutaneous sensitization to allergens and allergic diseases. We evaluated the effectiveness of an early-intervention algorithm for atopic dermatitis treatment, utilizing pimecrolimus for long-term maintenance therapy, in reducing transcutaneous sensitization in infants. This was a single-center cohort observational study that enrolled children aged 1–4 months with family history of allergic diseases, moderate-to-severe atopic dermatitis, and sensitization to ≥ 1 of the investigated allergens. Patients who sought medical attention at atopic dermatitis onset (within 10 days) were group 1 “baseline therapy with topical glucocorticoids with subsequent transition to pimecrolimus as maintenance therapy”; patients who sought medical attention later were group 2 “baseline and maintenance therapy with topical glucocorticoids, without subsequent use of pimecrolimus”. Sensitization class and level of allergen-specific immunoglobulin E were determined at baseline, and 6 and 12 months of age. Atopic dermatitis severity was evaluated using the Eczema Area and Severity Index score at baseline and 6, 9 and 12 months of age. Fifty-six and 52 patients were enrolled in groups 1 and 2, respectively. Compared with group 2, group 1 demonstrated a lower level of sensitization to cow’s milk protein, egg white and house dust at 6 and 12 months of age, and a more pronounced decrease in atopic dermatitis severity at 6, 9 and 12 months of age. No adverse events occurred. The pimecrolimus-containing algorithm was effective in treating atopic dermatitis and prophylaxis of early forms of allergic diseases in infants.